Government-held equity in foreign investment projects: Good for host countries? - Louis T. Wells (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2014)
Host governments have often sought some equity in mining and other foreign investment projects, but as shareholders they have rarely gained what they anticipated. Only in special cases might the benefits to governments outweigh the risks and often unanticipated costs governments encounter.
Keywords: 330